2012
DOI: 10.1109/emr.2012.6210514
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education: known worlds and new frontiers

Abstract: We explore three "worlds" that entrepreneurship educators generally teach in and introduce a new frontier where we discuss teaching entrepreneurship as a method. The method is a way of thinking and acting, built on a set of assumptions using a portfolio of techniques to create. It goes beyond understanding, knowing, and talking and requires using, applying, and acting. At the core of the method is the ability for students to practice entrepreneurship and we introduce a portfolio of practice-based pedagogies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
555
0
36

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(601 citation statements)
references
References 7 publications
10
555
0
36
Order By: Relevance
“…This confirms suggestions in the literature on entrepreneurship education that action-oriented courses may be more effective than theoretical courses (Gartner and Vesper 1994;Fiet 2000;Wee 2004;Cope 2005;Neck and Greene 2011) and preferred by prospective entrepreneurs (Ulrich and Cole 1987). Moreover, while Corbett (2007) demonstrated that individuals who learn by active experimentation tend to identify more opportunities than others, our results suggest that students at institutions with extensive, action-oriented education are also more likely to exploit these opportunities.…”
Section: Contribution To the Literature And Interpretation Of Main Resupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms suggestions in the literature on entrepreneurship education that action-oriented courses may be more effective than theoretical courses (Gartner and Vesper 1994;Fiet 2000;Wee 2004;Cope 2005;Neck and Greene 2011) and preferred by prospective entrepreneurs (Ulrich and Cole 1987). Moreover, while Corbett (2007) demonstrated that individuals who learn by active experimentation tend to identify more opportunities than others, our results suggest that students at institutions with extensive, action-oriented education are also more likely to exploit these opportunities.…”
Section: Contribution To the Literature And Interpretation Of Main Resupporting
confidence: 88%
“…Wee (2004) suggests to emphasize problem-based learning in curricula as it provides more effective, authentic learning situations. Also Neck and Greene (2011) advocate practice-based pedagogies that require students to use, apply and act.…”
Section: Modes Of Entrepreneurship Educationmentioning
confidence: 99%
“…There has been considerable debate (Neck and Greene, 2011;Pittaway and Cope, 2007) about whether enterprise skills can be learned, yet capability to be enterprising can be taught (Pilch and Shimshon, 2007, p. 16). In contrast to traditional entrepreneurship education -aimed at encouraging people to start a business (Jones and Iredale, 2010) -enterprise education develops enterprising skills, behaviours and attributes (Gibb, 1993), and equips learners to use these skills (Rae et al, 2012).…”
Section: Nature Of Enterprise Educationmentioning
confidence: 98%
“…In the context of these increasing demands from other subject areas (Rae, 2010), and criticisms of business schools (Carey and Matlay, 2010) for what Neck and Greene (2011) …”
Section: Nature Of Enterprise Educationmentioning
confidence: 98%
“…Entrepreneurship education (EE), defined as 'education for entrepreneurial attitudes and skills' (Bae et al 2014, p. 218), has been embraced by universities to increase students' entrepreneurial traits, knowledge and skills (Neck and Greene 2011;Mustar 2009;Kuratko 2005) to favor both their entrepreneurial engagement and their competitiveness in the labor market (Audretsch 2014;Urbano and Guerrero 2013;Debackere and Veugelers 2005). EE has undergone a progressive broadening of scope; in a report by the European Commission (2008, p. 7) it is emphasized that 'the benefits of entrepreneurship education are not limited to start-ups, innovative ventures and new jobs' but rather to 'an individual's ability to turn ideas into action and it is therefore a key competence for all, helping young people to be more creative and self-confident in whatever they undertake'.…”
Section: The Indirect Effect Of Internationalization On University Enmentioning
confidence: 99%